Determinants of Customer Satisfaction of Telkomsel Provider - Romadhoni, Buyung; Nasrullah, Nasrullah; Sahrullah, Sahrullah; Muchran, Muchriady (Dinasti Publisher, 2025)
The purpose of this study was to test the determinants of Telkomsel Provider customer satisfaction consisting of product quality, price, brand trust, and product innovation on customer satisfaction. Causal and quantitative analysis methods. The population in this study were Telkomsel card users in Makassar City. Based on the results of these calculations, the number of samples in this study was 97 respondents. This study used the Accidental sampling technique. The data collection method in this study was a questionnaire. The analysis method used in this study was Multiple Linear Regression Analysis. The results of the study found that product quality had a positive and significant effect on Telkomsel customer satisfaction in Makassar City, price had a positive and significant effect on Telkomsel customer satisfaction in Makassar City, brand trust had a significant effect on Telkomsel Provider Customer satisfaction in Makassar City, product innovationhave a significant impact on Customer satisfaction of Telkomsel Provider in Makassar City.